Graphing behaviour of heat transfer in terms of nusselt and reynolds / Mohd Rahimie Md Noor ...[et al.] - Md Noor, Mohd Rahimie; Mohd Fauzi, Nur Syafiqah Hidayah; Masrom, Siti Nur Fadhilah; Abdul Malek, Mohd Azry; Mustapha, Muhammad Firdaus; Mohd Yasin, Ahmad Bukhari (UiTM Cawangan Perlis, 2021)
Heat exchangers are tools used to transfer thermal energy between two fluids (liquid or gas) by convection and conduction at different level of temperatures. Heat exchangers are the common equipment and employed in many different applications because of ability to withstand high temperatures and compactness. There are no intermixing or leakage occurred between two fluids during the heat transfer process as fluids are separated by walls of heat exchanger. The main objective of this project is to determine the heat exchanger effectiveness in heat transfer performance. This will be done by investigating the performance of five different angles of heat exchanger which are 150,300, 450, 600 and 750. The effectiveness of heat exchanger depends on the convection heat transfer coefficient of the fluid. Besides that, this project also aims to develop some parameters such as Nusselt number, Reynolds number and Prandtl number for evaluating the heat transfer. It is found that the Nusselt Number at angle of 150 is lower compared to angle of 750. Meanwhile, Reynolds number for angle 150 is higher than angle 750 which means that the type of flow produced by angle 150 is turbulent flow while for 750 angle is laminar flow. Hence, the overall result of this project proved that 150 is the best angle for heat exchanger in chimney because of higher velocity, higher volume flow rate, higher density of gas and higher LMTD. The relationship between Nusselt number and Reynolds number between different angles can be observed by plotting the graph using Maple Software.